Women and Revolution: Maruxa Vilalta's 1910 - Magnarelli, Sharon (Latin American Theatre Review, 2003)
The "birth" of the modern Mexican nation is generally considered to be 1910, the start of the Mexican Revolution. That same revolution led to the creation of the PRI, which virtually controlled Mexican politics until Vicente Fox’s election to the presidency in 2000. In this paper, I analyze Maruxa Vilalta’s presentation of the women of the Mexican Revolution in her recent play, 1910. As depicted by Vilalta, the nation "born" of the founding revolutionary fathers not only accomplished very little for the majority of men, it did nothing to "free" women from their oppression by those "fathers" although it did effectively erase their role in that metaphoric "birth." (SM)